Visual and Biochemical Evidence of Glycocalyx Disruption in Human Dengue Infection, and Association With Plasma Leakage Severity - Lam, Phung Khanh; McBride, Angela; Le, Duyen Huynh Thi; Huynh, Trieu Trung; Vink, Hans; Wills, Bridget; Yacoub, Sophie (Frontiers in Medicine, 2020)
Background: Dengue is the most common arboviral infection globally; a minority of patients develop shock due to profound plasma leak through a disrupted endothelial barrier. Understanding of the pathophysiology underlying plasma leak is incomplete, but emerging evidence indicates a key role for degradation of the endothelial glycocalyx. Methods: We conducted an observational study in Vietnam to evaluate the sublingual microcirculation using sidestream darkfield imaging in 1) outpatients with confirmed dengue 2) patients hospitalized with dengue and 3) outpatients with other febrile illness (OFI). We estimated the glycocalyx degradation by measuring the perfused boundary region (PBR hf) and an overall microvascular health score (MVHS) with the software application GlycoCheckTM at enrolment, 48 hours later and hospital discharge/defervescence. We measured plasma syndecan1 and endocan at the same time-points. We compared PBR hf, MVHS, syndecan1 and endocan, between 1) outpatients with confirmed dengue versus OFI and 2) patients with dengue subdivided by clinical severity of plasma leak. Results: We included 75 patients with dengue and 12 outpatients with OFI. Images from 45 patients were analyzed using GlycoCheckTM. There was no significant difference in PBR hf or MVHS between outpatients with dengue and OFI. Median plasma syndecan1 was not significantly different in outpatients with dengue vs OFI, while median plasma endocan was significantly lower among patients with dengue vs OFI during the critical phase. In patients with dengue, PBR hf was higher in patients with Grade 2 vs Grade 0 plasma leakage during the critical phase (PBR hf 1.96µm vs 1.36µm for Grade 2 vs Grade 0 plasma leakage on days 4-6, respectively, p<0.001). Median levels of plasma syndecan1 and endocan were higher in Grade 2 vs Grade 0 plasma leakage, especially during the critical phase (Syndecan1 2613.8 ng/ml vs 125.9 ng/ml for Grade 2 vs Grade 0 plasma leakage on days 4-6, respectively, p<0.001, and endocan 3.21 ng/ml vs 0.16 ng/ml for Grade 2 vs Grade 0 plasma leakage on days 4-6, respectively). Conclusions: We present the first human in vivo evidence of glycocalyx disruption in dengue, with worse visual glycocalyx damage and higher plasma degradation products associated with more severe plasma leak.